(untitled) (Bulletin KNOB, 1992)
Within a period of about one year the State Service for the Preservation of Monuments has collected 265 wood-samples. About half of these could be dated. To enlarge the chance of dating different samples have been taken per construction- phase. The chance for dating also proved to be dependent of the place the wood was chopped and employed afterwards. Pending restorations well-worn materials often are removed, which spoiled the chance for dendrochronological dating. Information on the working process, marks etc., gets lost as well. Therefore the State Service for the Preservation of Monuments stands up for restorations with preservation of the old material or storage of a representative amount of beams. In the first quarter of the century at the restoration of the Church of St. Lebuïnus at Deventer all present roof coverings of the roman and gothic construction phases have been demolished: important starting points for the building’s history are lost. Historically considered the present roof has not been well constructed. Dendrochronology and the history of construction can contribute to the value judgement of a monument. Dendrochronology can sharpen the history of construction and architecture. By the presence of loose fragments of wood the towers of the Church of St. Servatius at Maastricht could be dated. Formerly a wooden roofing of the Church of Our Lady in the same town was reconstructed and dated. A detailed approach of the monument results in a better, more conscious weighing of preservation or demolishment of the present parts.